Wiara i przemoc - Tarnowski, Karol (Horyzonty Wychowania, 2017)
The author undertakes phenomenological deliberations referringto the relationship between faith and violence andattempts to reveal the „mechanism” which makes that power andfaith change into a „believing power”. Power may yield to temptationof ruling, abusing itself in the act of being exhilarated byitself. The power of some people may also delude with theprospect of unlimited ability to rule over the autonomy of others.Since it is not possible to rule over another person fully, due tothe sphere of freedom present in this person, violence must makeuse of fear. Such processes of delusion and intimidation arerealized in ideologies, reaching even metaphysical justificationsof fear: up till the argument of God of violence.The source of experience of faith is pre-trust, the affirmativeclinging on to the truth, opening a kind of pre-hope. Faith refersto a kind of reality, but it is given through intentional thoughtconstructs, through content: religious and cultural specifications,through gnosis which provides certainty. These are its externaltruths. Their contents state personalities. They attract emotionally,as embodiments of hope and truth of faith which is to orderlife according to the expected sense, which will allow to controlits meaninglessness. This is delusion, which still does not eliminatefalsehood or violence ... Therefore man has to protect hisfaith by thinking towards the ethos of internal truth of faith.Towards the affirmation of existence as such, which feeds onthinking faith and as a result caring about man’s dignity.